Non-invasive magnetopneumographic determination of lung dust loads in steel arc welders. Issue 4 (November 1981) - Freedman, A P; Robinson, S E; O'Leary, K; Goodman, L; Stellman, J M
Abstract : Magnetopneumography was used to measure non-invasively the concentration of the ferrimagnetic fraction of retained welding fume in the thoraces of steel arc welders. This was done by measuring the remanent magnetic fields due to ferrimagnetic particles. The 11 welders studied had concentrations of thoracic ferrimagnetic mineral several orders of magnitude greater than three machinists, 16 former asbestos insulators and 24 control subjects. These concentrations correlated well with total years welding (p less than 0.01) and radiographic evidence of small rounded densities (p less than 0.05), but not with smoking history. There was a higher concentration of ferrimagnetic mineral over the hilar regions. Magnetopneumography offers a non-invasive indicator of the accumulation of welding fume in the thorax.